An ecological value evaluation method based on ecological restoration: A case study of the Saihanba Mechanized Forest Farm in Chengde City - Chao Li; Feng Yang; Maomao Yan; Ying Qu (Chinese Journal of Population, Resources and Environment)
As China continues to develop its ecological civilization, it is crucial to quantitatively assess the ecological value to understand its potential impact on regional sustainable development. While previous studies have highlighted the importance of ecological value, they have not fully reflected the value of ecological restoration work or considered social costs and benefits, lacking a people-centered approach. Hence, this study analyzes the essence of ecological value from the perspective of sustainable development. By studying emblematic ecological restoration areas such as the Saihanba Mechanized Forest Farm in Chengde City, it aims to identify the significance of ecological restoration efforts in enhancing regional sustainable development capacity. The results underscore the necessity of comprehensively considering the value chain from ecological construction to ecological output, highlighting the value of ecological restoration in the ecological construction process as well as the well-being of people in the ecological output process. This approach assigns more economic and humanistic attributes to ecological value, thereby better serving the development of ecological restoration areas.